Encyclopedia Britannica world atlas (Encyclopedia Britannica, 2008)
" ... a comprehensive coverage of our planet ... complete with the full benefit of satellite imaging, laser measurement, and other modern and accurate mapping techniques. ... The extensive index has over 130, 000 place-names from the reference maps." - - back cover.